2021
DOI: 10.1093/brain/awab420
|View full text |Cite
|
Sign up to set email alerts
|

A review of Mendelian randomization in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a relatively common and rapidly progressive neurodegenerative disease which, in the majority of cases, is thought to be determined by a complex gene-environment interaction. Exponential growth in the number of performed genome-wide association studies (GWAS), combined with the advent of Mendelian randomization (MR) is opening significant new opportunities to identify environmental exposures which increase or decrease the risk of ALS. Each of these discoveries has the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 74 publications
0
50
0
Order By: Relevance
“…9,10 Single nucleotide polymorphisms (SNPs) related to a particular exposure are retrieved from the summary statistics of previous GWA studies and then used as a separate outcome GWAS to assess the relationship between the exposure and the outcome. 11 However, Mendelian randomization studies are not free from limitations, and three major assumptions must hold for the results to be valid: (i) genetic variants should be associated with the exposure (relevance assumption); (ii) they must not be associated with confounders (independence assumption); and (iii) they must not influence the outcome through other pathways than the exposure considered (exclusion restriction assumption). 8,9 The first assumption is usually quantified using the F-statistics, while the remaining two are addressed through sensitivity measures such as the MR-PRESSO and Cochran's Q test.…”
Section: Mendelian Randomization Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…9,10 Single nucleotide polymorphisms (SNPs) related to a particular exposure are retrieved from the summary statistics of previous GWA studies and then used as a separate outcome GWAS to assess the relationship between the exposure and the outcome. 11 However, Mendelian randomization studies are not free from limitations, and three major assumptions must hold for the results to be valid: (i) genetic variants should be associated with the exposure (relevance assumption); (ii) they must not be associated with confounders (independence assumption); and (iii) they must not influence the outcome through other pathways than the exposure considered (exclusion restriction assumption). 8,9 The first assumption is usually quantified using the F-statistics, while the remaining two are addressed through sensitivity measures such as the MR-PRESSO and Cochran's Q test.…”
Section: Mendelian Randomization Studiesmentioning
confidence: 99%
“… 9 , 10 Single nucleotide polymorphisms (SNPs) related to a particular exposure are retrieved from the summary statistics of previous GWA studies and then used as a separate outcome GWAS to assess the relationship between the exposure and the outcome. 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that a conservative threshold can lead to an underpowered test and paradoxical results. 9 , 19 In the current work, the risk of invalid SNPs was mitigated by robust MR measures and sensitivity analyses as described below. Identified SNPs within a 10 kb window were clumped for independence using a stringent cut-off of R 2 ≤0.001 within a European reference panel; where SNPs were in linkage disequilibrium (LD), those with the lowest P -value were retained.…”
Section: Methodsmentioning
confidence: 99%